Mukhabarah sebagai Problem Solver Umat - Nazaruddin, Nazaruddin (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2019)
The concept of Mukhabarah as a problem solver for the ummah and mukhabarah is also an Islamic intellectual legacy whose practice can be applied in the reality of people's lives. The application of the Mukhabarah in the era of modern society is carried out with a mechanism that is relevant to the existing development but remains consistent with the basis and values of Islamic ideality. This paper explores several things that are descriptive and exploratory with a sociological and welfare approach. The application of mukhabarah is limited to agriculture, however, this does not rule out the possibility of developing other fields with the basic principle of profit sharing. Mukhabarah aims to open up land that is not empowered to prosper land. Absorb labor to manage for those who do not own land, reduce the gap between capital and landowners and tenants, and boost land productivity. Mukhabarah shows that the concept still exists despite changing times by innovating operational techniques, institutionalizing the Mukhabarah to be practical and useful to the community generally, aims towards improving conditions by presenting Mukhabarah as a comprehensive solution for the people.